Redirection of Lamb Waves for Structural Health Monitoring. (5th January 2012) - Ong Ong, W. H. W. H.; Chiu Chiu, W. K. W. K.
Abstract : Currently, structures are designed without structural health monitoring (SHM) in mind. It is proposed that SHM should be addressed at the design stage of new structures. This paper explores the benefit which can be gained from such considerations. The scope encompasses Lamb-wave-based SHM and a given fatigue critical location (FCL). Optimization is performed using specialised ray tracing. A case study is carried out using a specimen that simulates a hard-to-inspect region in a fuel vent hole in wings structures of aircraft. This work will report on the potential use of the focussing of stress wave to improve detectability of defect in this hard-to-inspect location. Following optimization, results are produced numerically and experimentally. The results revealed sensitivity to damage is nearly doubled while minimum detectable damage size is significantly decreased. As a result, this study brings together an assortment of specialised tools to form a workflow ready for implementation.